2022
DOI: 10.3390/educsci12040275
|View full text |Cite
|
Sign up to set email alerts
|

Educational Gardens and Climate Change Education: An Analysis of Spanish Preservice Teachers’ Perceptions

Abstract: Educational gardens are powerful outdoor learning environments to address the subject of climate change and foster climate action. Using an online questionnaire, this study examines the influence of the main sociodemographic and academic factors, and the role of connectedness to nature, on the perception of educational gardens as contexts of climate change education (CCE) among Spanish preservice teachers (PSTs). The sample consisted of 889 PSTs enrolled in 9 university campuses of Spain. The statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 73 publications
2
1
0
Order By: Relevance
“…Regarding gender, the results suggest that women are more linked to activism than men, which supports previous studies by Vicente-Molina et al (2018) and Corrochano et al (2022) that indicate differences concerning this variable. On the other hand, the student body that shows some linkage with activism has the perception that the information offered by their university is greater, so it is found that greater access to information on climate change could influence activism, another specific objective achieved (SO2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding gender, the results suggest that women are more linked to activism than men, which supports previous studies by Vicente-Molina et al (2018) and Corrochano et al (2022) that indicate differences concerning this variable. On the other hand, the student body that shows some linkage with activism has the perception that the information offered by their university is greater, so it is found that greater access to information on climate change could influence activism, another specific objective achieved (SO2).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding gender, the results suggest that women are more linked to activism than men, which supports previous studies by Vicente-Molina et al . (2018) and Corrochano et al. (2022) that indicate differences concerning this variable.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is consistent with recent studies conducted in Ghana, Indonesia, and Ethiopia [20,31,32]. Studies have indicated that women have modestly stronger pro-environmental values than men [33][34][35]. In Korea, it was observed that pro-environmental behaviors among females are affected by their lifestyles and social norms [36].…”
Section: Determinants Of Household Waste Disposal Choices In Multivar...supporting
confidence: 90%
“…In line with similar studies, future teachers generally value the educational experiences in the context of the garden positively, especially to develop professional teaching skills (Hurtado-Soler et al 2020). They consider the garden as a valuable environment to learn science, and to address sustainability and climate change globally (Corrochano et al 2022). These results show it is important to continue using this resource in initial teacher training.…”
Section: Sdg -Sustainable Development Goalssupporting
confidence: 75%
“…However, it is necessary to continue improving the design of educational interventions in initial teacher training in order to face current challenges in a global and interrelated manner. Likewise, these interventions should integrate educational strategies and resources of Didactics of Sciences implemented in the garden to train students to design transformative proposals and act as true agents of change (Corrochano et al 2022).…”
Section: Conclusion and Proposals For Improvementmentioning
confidence: 99%